ENDOMORFISMA RIGID DAN COMPATIBLE PADA RING DERET PANGKAT TERGENERALISASI MIRING - Faisol, Ahmad (MATEMATIKA, 2014)
Given a ring R, a strictly ordered monoid and monoid homomorphism . Constructed the set of all function from S to R whose support is artinian and narrow, with pointwise addition and the skew convolution multiplication, it becomes a ring called the skew generalized power series rings (SGPSR) and denoted by . A ring R is called reduced if it contains no nonzero nilpotent elements, reversible if for all , implies . Let be a ring endomorphism, if for , implies , then is called rigid. If for all , if and only if , then is called compatible. In this paper we will discuss about the constructing of SGPSR homomorphism. Beside that, we also discuss about rigid and compatible endomorphism on SGPSR .